The Effects of Dietary Neutral Detergent Fiber Ratio from Forage and Concentrate on The Dietary Rumen Degradability and Growth Performance of Philippine Native Goats (Capra hircus Linn.) - Dwiatmoko Nugroho; Sunarso Sunarso; Cesar C. Sevilla; Amado A. Angeles (Chemical Engineering Diponegoro University, 2014)
This research’s objective was to determine the dietary rumen degradability and growth performances of goats fed dietary treatments. 18 native female goats (live weight of 7.96 ± 2.21 kg) were grouped into 6 classes for the feeding trial and 3 male mature goats with rumen cannula were used for the in situ digestibility. The three dietary treatments were: T1 - 72:28 Forage-Concentrate NDF ratio; T2 - 64:36; and T3 - 57:43. The rate of rumen degradability of DM and CP at 0 hours, potentially degradable fraction (b) and the rate of degradation of b were not affected by dietary treatments. The different ratios of NDF in the diets significantly affected the intake of DM, CP and NDF from forage and concentrates. Treatment diets affected the total intake of DM, CP and NDF of the animals. However, growth performance was not affected by the treatments showing the same production efficiency. This means that diets given to native goats with ratio of forage NDF of 72.07% can be applied since the value of the output and efficiency of feed utilization had the same value compared to diets ratio of forage NDF of 57.21%.